Inhibition of miR-185-3p Confers Erlotinib Resistance Through Upregulation of PFKL/MET in Lung Cancers - Li, Ke; Zhu, Xinling; Yuan, Conghu (Frontiers in Cell and Developmental Biology, 2021)
Erlotinib (ER), as an epidermal growth factor receptor (EGFR) tyrosine kinase inhibitor (TKI), has a significant therapeutic effect in lung cancers. However, EGFR TKI resistance inevitably occurs after treatment for approximately 12 months, which weakens its antitumor effect. Here, we identified miR-185-3p as a significantly downregulated microRNA responsible for acquired EGFR TKI resistance in cells and patients with lung cancer. qRT-PCR and Western Blot were performed to determine the relative expression of miR-185-3p in ER-resistant tumor tissues and cells. The viability and apoptosis of lung cancer cells were evaluated by Cell Counting Kit-8 (CCK8) assay and flow cytometry, respectively. The binding between miR-185-3p and liver-type phosphofructokinase (PFKL) was verified by dual luciferase assay. It was found that overexpression of miR-185-3p conferred ER sensitivity in lung cancer cell lines. MiR-185-3p was downregulated in ER-resistant lung cancer cells (H1299/ER and A549/ER). MiR-185-3p inhibited proliferation and induced cell apoptosis in ER-resistant cells. Mechanistically, miR-185-3p downregulation contributed to ER resistance through upregulating the PFKL. Moreover, Mesenchymal to epithelial transition (MET) oncoprotein promoted EGFR-TKI resistance by regulating miR-185-3p and PFKL. These findings revealed a novel mechanism in which downregulation of miR-185-3p may induce overexpression of PFKL and MET and confer ER resistance in lung cells. Combination of PFKL/MET inhibitors and EGFR TKIs could be a rational therapeutic approach for lung cancer patients with EGFR mutation.